2009
DOI: 10.1021/jp8089209
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity of Gold−Platinum Clusters for Low Temperature Fuel Cell Applications

Abstract: The electrocatalytic activity of gold-platinum (Au-Pt) clusters was investigated in acidic and alkaline electrolytes. The clusters were synthesized by electrodeposition on fluorinated tin oxide (FTO) substrates and carbon disks with dimensions from 50 to 200 nm. Methanol electrooxidation (fuel cell anode) and oxygen electroreduction (fuel cell cathode) activities were measured using cyclic voltammetry and chronoamperometry. The results for methanol electrooxidation showed that platinum could be partially subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 61 publications
7
59
0
Order By: Relevance
“…The stabilization of the catalyst can be attributed to the reduction of surface oxidation from Au in the sublayer, therefore inhibiting the dissolution of metal. The stabilizing effects of Au on Pt nanoparticles have been reported by Zhang et al [44] and other studies [43,45,46] have also demonstrated the same effect of Au. The addition of a Pd-Au alloy between Pt ML and Pd/C core enhance both the activity and stability for ORR from the induced lattice contraction (both lateral and radial).…”
Section: Ptsupporting
confidence: 69%
“…The stabilization of the catalyst can be attributed to the reduction of surface oxidation from Au in the sublayer, therefore inhibiting the dissolution of metal. The stabilizing effects of Au on Pt nanoparticles have been reported by Zhang et al [44] and other studies [43,45,46] have also demonstrated the same effect of Au. The addition of a Pd-Au alloy between Pt ML and Pd/C core enhance both the activity and stability for ORR from the induced lattice contraction (both lateral and radial).…”
Section: Ptsupporting
confidence: 69%
“…Cationic Au-Pt clusters have shown unique reactivity for C-N coupling of methane and ammonia. 11,12 Recently it has been reported that carbon-supported Au-Pt bimetallic NPs display performances better or similar to those of pure platinum supported on carbon for oxygen reduction, 13,14 provided alloyed and not phasesegregated Au-Pt NPs are used. It has been also shown that platinum could be partially substituted by gold for application in methanol oxidation: higher resistance to poisoning was observed in acidic media with Au-Pt bimetallic NPs, while in alkaline environment a significant overall improvement in performance was reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also shown that platinum could be partially substituted by gold for application in methanol oxidation: higher resistance to poisoning was observed in acidic media with Au-Pt bimetallic NPs, while in alkaline environment a significant overall improvement in performance was reported. 14 The main remaining challenge is that the preparation of alloyed Au-Pt NPs either requires severe thermal treatments, generally yielding aggregated particles, or follows milder but complicated routes to obtain nanostructured materials. 15,16 Typically, these milder procedures involve the use of dendrimer complexes 15 or phase transfer agents and encapsulating agents together with thermal treatment in the latter case.…”
Section: Introductionmentioning
confidence: 99%
“…This is Figure 5 shows the energy diagram for the methanol decomposition on PtAu 2 cluster starting from O-H bond scission pathway. Figure 6 gathers the geometries of intermediates (IM15-IM19) and transition states (TS [15][16] , TS [16][17] , and Ts [18][19] involved along this pathway. We find that the mechanism details for the reaction over binary PtAu 2 cluster are very similar to that over monometal Pt 3 10.03, 11.45, and 11.96 kcal mol -1 , the methanol is finally oxidized into CO molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Many Ptbased bimetallic catalysts, such as PtRu [2][3][4], PtAu [5][6][7], PtCo [12], PtMo [13], and PtSn [14,15], have been found to have higher activity for the methanol dehydrogenation reaction with improved resistance to CO poisoning than pure Pt catalysts, and have been applied successfully to prototypes of commercial DMFCs. In particular, PtAu bimetallic nanoparticles, which have attracted much attention over the past twenty years [16,17], have been proposed as excellent electrocatalysts for methanol electrooxidation [5,[18][19][20][21][22][23] because Au is more stable than nonnoble metals under the DMFCs operating conditions and relatively less expensive than other noble metal materials.…”
Section: Introductionmentioning
confidence: 99%